The measurement of the slurry rheology from the discharge of a rotary grinding mill - Bailie, Darrell Stephen (My University, 2016)
In South Africa mineral processing is a very important activity and ""lith declining om grades and increased need for foreign' revenue it is necessarv to develop methods which wUl keep are processing'~osts as low as possible. (( Milling is an example of a capital intensive unit operation 'which has much scope for more efficient Operation. Better control of the viscosity of the slurry discharged from a rotary 9rir~ding mill will result in improved milling efficiency and hence a saving 1'1electricity ~nd steel costs will be experienced. More effective and conslstent grinding in the mil! will also result in em lmproved mineral recovery. Slurry rheology is the variable of interest in monitoring and controlling a wet grinding mill rather than other rneascres of slurry composition presently used (eg percent solids). Up to this point in time however this variable has not been successfully used due to the fact that a sufficiently reliable and robust device for measuring the viscosities of slurries on an on-line basis has riot been available, This project was undertaken to develop just such a device (which is in the process of being patented bV Professor M H Mays). The flow rate of a fluid down a vertical tube is a function if its viscosity as well as ether quantifiable variables. This is the basis of the operation of the measurement device. Useful features of this device Include the fact tl'tat it has no movin~ paris, is inexpensive and robust and is subject tli) little wear. ''rha measurement can b --------------------------------------.--~~-----~------ performed directly on the stream in question and it is unlikely to be blocked up by fibres/particles. A self cleaning facility may also be Included. Ba$ed On the experimental results the technique shows much promise and it is anticipate:ted that the basic design could easily evolve into a useful, practical devi~e for th~ measurement of the apparent viscosity of settling slurries as well as other fluids. If a differential pressure tell" Is also connected to the device it may be used to obtain the density of the fluid being sampled. A model based on the. principles of conservation of momentum was developed and solved numerically using MATLAB {which uses 5th order Runge Kuttal as well as a Turbo pascal program using 4th order Runge i<utta. The model was also' simp.lified slightly by neglecting acceleration of th~ flui¢ (a simplificatlcbn which was shown ~xperimentally to hold) and solved analytically. The results predict~d by the model ~3~ffar only slightly from the experimentally determined i' results. The devil~e has been tested on pilot mills at MINTEK's research facility as wall as the Anglo American Research labs, with varying degrees of success.
Keywords: Slurry--Fluid dynamics; Viscous flow; Rheology